2018
DOI: 10.21776/ub.jitek.2018.013.01.6
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristic of Fermented Goat Milk Added with Different Starters Lactic Acid Bacteria

Abstract: Development of traditional food including dadih to be commercial fermented milk was needed to achieve efficiency and effective of products. Dadih with natural starter needs to be changed with ABSTRAKDadih merupakan produk susu fermentasi pengembangan makanan tradisional menjadi produk komersial yang efisien dan efektif. Dadih menggunakan starter natural dan saat ini starter yang digunakan diisolasi ditingkatkan untuk diproduksi secara komersial. Penelitian ini bertujuan untuk mengevaluasi Lactic Acid Bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…The water content in yoghurt is affected by the activity of lactic acid. Make the starter produce high lactic acid, precipitate milk protein, and decrease moisture content at the end of fermentation (Wati et al, 2018).…”
Section: Proximate and Dietary Fibre Analysis Of Mung Beans Yoghurtmentioning
confidence: 99%
“…The water content in yoghurt is affected by the activity of lactic acid. Make the starter produce high lactic acid, precipitate milk protein, and decrease moisture content at the end of fermentation (Wati et al, 2018).…”
Section: Proximate and Dietary Fibre Analysis Of Mung Beans Yoghurtmentioning
confidence: 99%
“…Table 1 shows the values of pH, Titration Acidity, protein, fat and ash content for the butter milk treatments.The results of the statistical analysis showed that there were no significant differences at the probability level of <0.05 for the pH values, which reached the highest value of 4.37 for fermented Buttermilk with the starter YO-MIX 495, and there were significant differences in the values of the Titration Acidity that reached the highest value of 0.84% with the starter YO-MIX 505, and there were no differences significant in protein content. The fat and ash were at a probability level of P<0.05, where the highest percentage of protein was 2.73%, fat 1.24% with YO-MIX 505 starter, ash 0.65% with YO-MIX starter 495.The reason is due to the ability of the starter bacteria to convert the sugar lactose into lactic acid and other organic acids, which lowers the pKa value inside the cell and makes its membrane more permeable to substances such as lactate and acetate, which leads to a decrease in the pH value and an increase in the total Titration Acidity [18].The results also showed that there were differences in Titration Acidity, pH and chemical content between the types of starters.It was noticed [19] that there was a difference in the chemical content of buttermilk when using different primers. When adding the primers 11, 21, 25, 29 and 41 to ferment goat milk, when using starter 21, it gave the highest water content of 91.21%, which negatively affected the ash content of 0.70 % and fat 1.03% due to the low activity of this starter that affected the total solids.…”
Section: Ph Surface Titration Acidity and Chemical Contentmentioning
confidence: 99%
“…Based on the research results, it is known that the higher the total dissolved solid the lower the syneresis and the higher the viscosity. Syneresis is likewise negatively related to viscosity, with low syneresis indicating high viscosity (Wati et al, 2018). Adane Shegaw et al, (2020) reported that camel milk yogurt without adding EPS had the highest syneresis of 71% compared to yogurt with EPS addition, which was 67%.…”
Section: Syneresismentioning
confidence: 99%